The influence of marketing scholarship's legacy on nonprofit marketing - Walter Wymer (International Journal of Financial Studies, 2013)
This inquiry contributes to the literature on the development of 'nonprofit marketing thought' by describing how the field's early period established a legacy effect on nonprofit marketing scholarship to the present day. This qualitative work uses a wide variety of sources from a protracted historical period in order to more fully inform a perspective on the relevant issues that have influenced the development of nonprofit marketing scholarship. The investigation suggests that, although the debate on whether or not marketing is a science was nominally resolved years ago, the origins of marketing scholarships as an applied business discipline remain influential. The effects on this influence is a body of research that is fragmented, conflicted, sometimes invalid, and has produced few general theories indicative of a social science. Recommendations are offered for improving the quality of nonprofit marketing scholarship.
Keywords: M39; L39; 330; marketing history; marketing theory; nonprofit marketing; nonprofit marketing scholarship; nonprofit marketing research